Green Accounting: Analisis Penerapan Green Innovation Pada Pengelolaan Limbah Pabrik Tahu di Kartasura - Nur Afra Hana Annisa Putri; Alviani Indraswari; Yahya Wulandari; Ronnawan Juniatmoko (Jurnal Akuntansi dan Audit Syariah)
The tofu industry is currently expanding in Indonesia, especially in Purwogondo Village, Kartasura District. In the village, the majority of the population produces tofu. Tofu production is still carried out using traditional and simple technology. This causes the level of efficiency in the use of water and raw materials is still low but the level of waste production is also relatively high. The human resources involved or the workers in general have a relatively low level of education, so that neither workers nor the tofu industry itself has properly managed waste. This research was conducted at Mr. Parji's Tofu Factory which is one of the tofu factories in Purwogondo Village, Kartasura District, the study aims to analyze the effect of implementing green accounting through the green concept innovation on the waste management of Mr. Parji's tofu factory. The research method used is descriptive qualitative, namely by means of observation, direct interviews with relevant informants and documentation studies in the form of pictures. The results obtained from the research that have been carried out show that the application of green innovation to the tofu factory waste Mr. the surrounding environment will not be polluted, while for the tofu factory liquid waste is left in a shelter so that it just flows into the river, but the water that seeps from the shelter can fertilize the plants in the surrounding environment.